PENGARUH RETURN ON ASSET DAN NET PROFIT MARGIN TERHADAP RETURN SAHAM (Studi Kasus Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021) - Eddy Soegiarto, Camelia Verahastuti, dan Yohana Horet (Prodi Ilmu Administrasi Negara, 2022)
The purpose of this study is to find out and analyze the influence 1). Return onAsset (ROA) against Stock Return on mining companies listed on the Indonesia StockExchange in 2019-2021, 2). Net Profit Margin (NPM) against Stock Return in miningcompanies listed on the Indonesia Stock Exchange in 2019-2021.The theoretical basis used in this research is financial accounting. The analyticaltool used is the formula for Return On Assets, Net Profit Margin and Stock Return. Thetype of research used is quantitative research obtained from secondary data. Withpurposive sampling as a sampling method. The data analysis technique in this research isusing multiple linear regression analysis with the help of the statistical computerapplication program SPSS (Statistical Package For Social Science).Based on the results of data analysis and discussion, it can be concluded that theresults of the study 1). Return On Assets has a positive and insignificant effect on StockReturns in mining companies in 2019-2021 because from the analysis of test value t 0.051or 5,1%, the calculated t value is 0.225 < t table 2,042 with a significant rate of 0.824 > 0.05.2). Net Profit Margin has a positive and insignificant effect on Stock Returns in miningcompanies in 2019-2021 because from the analysis of Test Value t 0,068 or 6,8%, thecalculated t value is 0,303 < t table 2.042 with a signification rate of 0.764 > 0.05.